2019
DOI: 10.1364/ol.45.000097
|View full text |Cite
|
Sign up to set email alerts
|

High-power ytterbium-doped fiber laser delivering few-cycle, carrier-envelope phase-stable 100 µJ pulses at 100  kHz

Abstract: We present a carrier-envelope phase (CEP)-stable Yb-doped fiber laser system delivering 100 µJ few-cycle pulses at a repetition rate of 100 kHz. The CEP stability of the system when seeded by a carrier-envelope offset-locked oscillator is 360 mrad, as measured pulse-to-pulse with a stereographic above-threshold ionization (stereo-ATI) phase meter. Slow CEP fluctuations have been suppressed by implementing a feedback loop from the phase meter to the pulse picking acousto-optic modulator. To the best of our know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 32 publications
0
10
0
2
Order By: Relevance
“…It was also shown that soliton-effect self-compression in gas-filled PCF can be used to generate CEP-stable pulses in the single-cycle regime at 800 kHz repetition rate with only 1 µJ pump pulses from an optical parametric amplifier [15]. Implementing CEP-stabilization schemes as described in [42], we expect that phase-stable pulses can be generated also with our system. This would enable many exciting experiments, for example in phase-sensitive ultrafast spectroscopy and strong-field physics, with a simple setup at unprecedented repetition rate and power.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…It was also shown that soliton-effect self-compression in gas-filled PCF can be used to generate CEP-stable pulses in the single-cycle regime at 800 kHz repetition rate with only 1 µJ pump pulses from an optical parametric amplifier [15]. Implementing CEP-stabilization schemes as described in [42], we expect that phase-stable pulses can be generated also with our system. This would enable many exciting experiments, for example in phase-sensitive ultrafast spectroscopy and strong-field physics, with a simple setup at unprecedented repetition rate and power.…”
Section: Discussionmentioning
confidence: 82%
“…Obtaining a precisely-defined single-cycle optical waveform requires fine control of the pulse carrier-envelope phase (CEP). Recently, it was shown that CEP-stable few-cycle pulses can be generated at 100 kHz repetition rate from a 300 µJ ytterbium fiber laser by two-stage nonlinear compression in gas-filled hollow capillary fibers [42]. It was also shown that soliton-effect self-compression in gas-filled PCF can be used to generate CEP-stable pulses in the single-cycle regime at 800 kHz repetition rate with only 1 µJ pump pulses from an optical parametric amplifier [15].…”
Section: Discussionmentioning
confidence: 99%
“…This is the highest pulse energy of attosecond pulses with temporal characterization achieved so far on target using a laser with a repetition rate higher than 10 kHz and an average power in 100 W regime. As a future step, we plan to compress the laser pulses further to a few-cycle duration [76]. We expect that this approach will even increase the conversion efficiency and the flux of the attosecond pulses.…”
Section: Discussionmentioning
confidence: 99%
“…This is the highest pulse energy of attosecond pulses achieved so far on target using a laser with a repetition rate higher than 10 kHz and an average power in 100 W regime. As a future step, we plan to compress the laser pulses further to a few-cycle duration [43]. We expect that this approach will even increase the conversion efficiency and the flux of the attosecond pulses.…”
Section: Discussionmentioning
confidence: 99%